Prevederi ale Legilor Generale de Asigurări Sociale de Pensii adoptate în România, anii 2000, 2010 şi 2019 - Mărginean, Ioan (Calitatea Vieții, 2019)
This article reviews the regulations of the pension laws in Romania over the postcommunist period. It aims to analyze the implications of these regulations and the changes that occured over time. The pension law of 2000 was passed rather late, the one in 2010 can be considered less necessary, while the most recent of 2019 includes a major modification by equalising pensions for women and men with the same work record.